Uso da terra e clima urbano e suas influências sobre a população de Euglossini na cidade de Parnaíba, PI, Brasil - Oliveira, Benedito Gledson de Araújo [UNESP] (2015)
Nowadays urban growth has generated significant impacts on the environment, mainly as a result of its disorderly expansion without more precise preliminary studies related to urban management. The Euglossini bees are found within neotropical regions, with exclusive pollinators of several plant species. Their presence in the environment is linked to the existence of certain plant families, especially orchids. These bees are highly vulnerable to human activities. This study aimed to analyze the land use and urban climate and its influence on the population of Euglossini. The survey was conducted within the city limits of the city of Parnaíba - PI. Being the second largest city in the state to the city of Parnaíba is classified as medium-sized which is currently undergoing a marked urban growth leveraged by human activity related to trade and construction. The methodology was a survey of the actual temperature data, relative humidity, occurred in the four collection points for 14 days, seven consecutive days in the rainy season (from 22 to 28 April 2013) and seven days in the dry season (September 29 until October 5, 2013). Field collection effort time was 12 hours daily, from 7:00 until 19:00 hours, so a total of 168 hours. This time in each area were recorded data on temperature and relative humidity in seven times during the day, for this the following times it was stipulated: 7:00, 9:00, 11:00, 13:00, 15: 00, 17:00, 19:00. Similarly parallel bees were collected in four areas, so being this close, traps were used to capture and termohigrômetros for temperature records and relative humidity at the time of capture. Also maps were made by obtaining satellite images using the MultiSpec programs and QuantumGIS version 2.10. In the resort of Dirceu Arco Verde, being located near the rural area, there is the prevalence of milder temperatures with a very high relative humidity during the rainy season, but in winter remains at levels above ...